PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU PADA SEKOLAH DASAR NEGERI 006 PERAWANG BARAT - rupat, herman (Sekolah Tinggi Ilmu Ekonomi Riau, 2019)
The research was conducted at Elementary School 006 Of Perawang Barat. The purpose of this study is to determine the influence of Principal Leadership on Teacher Performance at Elementary School 006 Of Perawang Barat. The research method is descriptive with quantitative approach, with the research population is teachers of Elementary School 006 Of Perawang Barat as many as 43 teachers. While the number of samples determined in this study is the entire population minus 1 principal so that a total of 42 teachers. Based on simple linear regression equation Y = 22,609 + 0,744X. hence seen constants equal to 22,609, so influace of principal leadership on teacher performance is positive proven b = 0,744 meaning that every increase of headmaster leadership one unit will increase teacher performance at Elementary School 006 Of Perawang Barat at 1,235. The Leadership variable with tcount 4,264 > ttable 2,021 with significant level 0.000 less than 5%. Then Ho is rejected and Ha accepted, meaning the leadership variable of principal has a positive and significant effect on teacher performance in Elementary School 006 Of Perawang Barat. The value of R-square (coefficient of determination) is 0,313, this indicates that the principal's leadership contributes to the teacher performance in Elementary School 006 Of Perawang Barat by 31,3%, while the rest (100% - 31,3%) = 68,7% influenced by other variable outside of variable in this research.